Inside Back Cover: Protein Adsorption Switch Constructed by a Pillar[5]arene‐Based Host–Guest Interaction (Chem. Eur. J. 3/2016). Issue 3 (8th January 2016) - Xiao, Xuan; Nie, Guanrong; Zhang, Xiaoyan; Tian, Demei; Li, Haibing
Abstract : The interfacial properties of solid substrates are of importance for protein adsorption. A reversible protein adsorption switch based on the host–guest interaction of the butoxy pillar[5]arene and adipic acid is reported. Through the detection of the contact angle, AFM and luminoscope measurements on the silicon substrate, the intelligent protein switch was found to exhibit excellent adsorptivity for BSA and switch performance by pH regulation. This system holds the possibility for wide applications in the production of new biosensors, immunological tests, and drug delivery. More information can be found in the Full Paper by H. Li et al. onpage 941 ff.